(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The purpose of this paper is to develop a new paradigm for a fuzzy dynamic programming for solving the shortest route problem. Dynamic programming is a mathematical technique used for obtaining the solution for a sequence of interrelated decisions. In real life, situations are not crisp enough moreover, they are fuzzy in nature. Therefore, in order to deal with the real situations a new method is being proposed here to find the more realistic answers to the dynamic problems. For this purpose the MATLAB software is used where the decision parameters are trapezoidal fuzzy numbers.